The Contribution of the Prague Rules to Promoting Efficiency in International Arbitration - Stephens-Chu, Gisèle (2020)
The Prague Rules are intended to provide efficiency and reduce costs in conducting arbitration proceedings. The Rules are based on the position that the practice and procedure of international arbitration is too heavily influenced by the adversarial system found in common law jurisdictions, and that the inquisitorial judicial practices of civil law jurisdictions are more conducive to a “streamlined procedure”. In this paper, the authors first consider whether this predicate is accurate and fair. Are adversarial practices the source of inefficiency in international arbitration, or can the reasons be found elsewhere? Next, they compare certain features of the Prague Rules to the IBA Rules on the Taking of Evidence, and examine how both sets of rules differ in substance. Moreover, they address the criticisms that the Prague Rules may pose yet another case of useless rule-making. In fact, the authors critically assess the consequences of an active role of arbitral tribunals in case management and the appropriateness of a controlled use of documentary production, witness evidence (particularly in oral testimony) and appointment of experts.